Застосування методів комплексного аналізу в задачах гідродинаміки - Дудар, М. А. (ХНУРЕ, 2023)
The paper considers the application of complex analysis methods to the solving of the problem of flowing (non-circulating and circulating) of a circular cylinder by a flow of ideal (inviscous) fluid. The corresponding complex potential is obtained and stream lines are constructed for different values of circulation.
Keywords: стаціонарна безвихорева плоска течія; нестислива рідина; поле швидкості; задача обтікання циліндричного тіла